2017
DOI: 10.3389/fmicb.2017.00713
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Cinnamaldehyde, Carvacrol, and Eugenol Reduce Campylobacter jejuni Colonization Factors and Expression of Virulence Genes in Vitro

Abstract: Campylobacter jejuni is a major foodborne pathogen that causes severe gastroenteritis in humans characterized by fever, diarrhea, and abdominal cramps. In the human gut, Campylobacter adheres and invades the intestinal epithelium followed by cytolethal distending toxin mediated cell death, and enteritis. Reducing the attachment and invasion of Campylobacter to intestinal epithelium and expression of its virulence factors such as motility and cytolethal distending toxin (CDT) production could potentially reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 71 publications
6
57
0
Order By: Relevance
“…2). This observation agrees with previously reported studies, wherein soft agar containing sublethal Car, TC, or Eug were found to significantly (P Ͻ 0.05) reduce the motility of S. Typhimurium and C. jejuni (8,22).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2). This observation agrees with previously reported studies, wherein soft agar containing sublethal Car, TC, or Eug were found to significantly (P Ͻ 0.05) reduce the motility of S. Typhimurium and C. jejuni (8,22).…”
Section: Resultssupporting
confidence: 93%
“…Essential oils (EOs) are gaining popularity in recent years, due to their natural origin, wide-spectrum antimicrobial activities, and generally recognized as safe (GRAS) status for food usage (4). In particular, thymol (Thy), carvacrol (Car), and trans-cinnamaldehyde (TC), the principal compounds of thyme, oregano, and cinnamon EOs, respectively, have been demonstrated to possess good antimicrobial activities against various foodborne pathogens, including E. coli O157:H7 (5), Staphylococcus aureus (6), Salmonella enterica serovar Typhimurium (7), Pseudomonas aeruginosa (3), and Campylobacter jejuni (8).…”
mentioning
confidence: 99%
“…Carvacrol treatment starting 4 days prior murine infection could sufficiently lower intestinal C. jejuni burdens up to 2 orders of magnitude until day 6 p.i. The antimicrobial properties of carvacrol directed against food-borne pathogens such as C. jejuni [26,29,30,37] Salmonella spp. [37,[43][44][45], Escherichia coli O157:H7 [46] and Bacillus cereus [47,48] have been shown in vitro recently.…”
Section: Discussionmentioning
confidence: 99%
“…Both, in vitro and in vivo studies revealed that carvacrol application could effectively reduce C. jejuni loads in intestinal samples derived from chicken [25][26][27][28]. Furthermore, carvacrol could effectively reduce virulence gene expression and invasion of C. jejuni into chicken cells [26,29]. Most importantly, the finding that carvacrol application resulted in inhibition of motility and invasive properties of C. jejuni in vitro points towards carvacrol as a promising candidate molecule for the combat of human campylobacteriosis [30].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Sulaeman et al (2012) showed a link between the expression of the cadF gene, which encodes an outer membrane protein, and C. jejuni adhesion. Compounds that reduced the expression of cadF, such as trans-cinnamaldehyde, carvacrol and eugenol, also reduced C. jejuni adhesion to abiotic surfaces (Upadhyay et al 2017;Wagle et al 2019); thus, alterations to the C. jejuni membrane can be considered as one of their mechanisms of antiadhesion action.…”
Section: Adhesion Mechanisms and Identification Of Targets Against Admentioning
confidence: 99%